2015
DOI: 10.2147/ndt.s91625
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontocerebellar transcranial direct current stimulation increases amplitude and decreases latency of P3b component in patients with euthymic bipolar disorder

Abstract: IntroductionNeurocognitive impairments have been observed in patients with bipolar disorder (BD) even during the euthymic phase of the disease, potentially representing trait-associated rather than state-associated characteristics of the disorder. In the present study, we used transcranial direct current stimulation (tDCS) applied to cerebellar and prefrontal cortices to improve the neurophysiological performances of patients with euthymic BD.MethodsTwenty-five outpatients with BD underwent open-label prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In general, anodal stimulation is believed to enhance motor and cognitive functions, whereas cathodal stimulation typically inhibits functioning. However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ).…”
Section: Technical Issuesmentioning
confidence: 67%
See 1 more Smart Citation
“…In general, anodal stimulation is believed to enhance motor and cognitive functions, whereas cathodal stimulation typically inhibits functioning. However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ).…”
Section: Technical Issuesmentioning
confidence: 67%
“…Cerebellar tDCS studies using an online protocol applied tDCS during a variety of tasks: in the adaptation phase of a motor learning protocol (Galea et al, 2009 ; Jayaram et al, 2012 ; Block and Celnik, 2013 ; Hardwick and Celnik, 2014 ; Herzfeld et al, 2014 ; Avila et al, 2015 ; Calzolari et al, 2015 ; Panouillères et al, 2015a , b ; Yavari et al, 2016 ) during the learning/(mental) practicing of a task (Foerster et al, 2013 ; Shah et al, 2013 ; Dutta et al, 2014 ; Cantarero et al, 2015 ; Van Wessel et al, 2016 ; Wessel et al, 2016 ) or during the acquisition phase of a conditioned response (Zuchowski et al, 2014 ). Most studies, however, used an offline application of cerebellar tDCS, especially when clinical study populations were involved (Grimaldi and Manto, 2013 ; Bradnam et al, 2014 ; Gironell et al, 2014 ; Grimaldi et al, 2014b ; Ho et al, 2014 ; Benussi et al, 2015 ; Bersani et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Bation et al, 2016 ; Ferrucci et al, 2016 ). In only one study, performed by Calzolari et al ( 2015 ), online cerebellar stimulation was used in a single patient, applying cerebellar tDCS during a prism adaptation task.…”
Section: Technical Issuesmentioning
confidence: 99%
“…These studies demonstrated the feasibility of EEG-based classification that might help better select patients who would further benefit from tDCS treatment in both alleviating depressive symptoms and neurocognitive functioning. Bersani et al examined the effects of repeated prefrontal-excitatory and cerebellar-inhibitory tDCS on P300 novelty task in euthymic bipolar patients [ 32 , 33 ]. P3b reflects working memory update of change while subjects pay attention to stimulus, while P3a is elicited by unexpected stimulus and is thought to reflect automatic reorienting [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the direction of electrode polarization is critical in terms of the after-effects. Through stimulation of the motor cortex, tDCS can be used for: chronic pain (Deer et al 2014;Souto et al 2014;Hodaj et al 2016), pain after endoscopic retrograde cholangiopancreatography (Borckardt et al 2011), trigeminal pain including refractory orofacial pain (Antal et al 2010;Hansen et al 2011;DosSantos et al 2012;Hagenacker et al 2014;Fricova et al 2016;Kreuzer et al 2017), fibromyalgia (Valle et al 2010;Cummiford et al 2016;Castillo-Saavedra et al 2018), major depression (Vigod et al 2014;Tortella et al 2015;Brunoni et al 2016;Liu et al 2017), bipolar disorder (Bersani et al 2015;Pereira-Junior et al 2015;Tortella et al 2015), schizophrenia (Agarwal et al 2013;Palm et al 2016;Gögler et al 2017), Alzheimer's disease (Nardone et al 2012;Bystad et al 2016;Narita and Yokoi 2017), modulation of associative learning (Branscheidt et al 2017), Parkinson's disease (Benninger et al 2010;Hendy et al 2016;Schabrun et al 2016), pain after stroke (Schjetnan et al 2013;Chhatbar et al 2016;Russo et al 2017) and tinnitus (Garin et al 2011;…”
Section: Nibs: Transcranial Electrical Stimulationmentioning
confidence: 99%